The Influence of Work Environment and Job Placement on Employee Performance Mediated by Job Satisfaction in the Regional Secretariat Protocol in Banten Province - Alsyauqi, Abdurrahman Daf'a; Yusuf, Furtasan Ali; Nuryanto, Uli Wildan (Amkop Management Accounting Review (AMAR), 2025)
The declining performance of protocol staff at the Regional Secretariat in Banten Province in recent years has become a strategic issue that requires further investigation. Factors such as mismatched job placements, lack of professional training, and an unconducive work environment have contributed to the decline in the quality of public services. This study aims to analyse the influence of the work environment and job placement on employee performance with job satisfaction as a mediating variable. The method used was a quantitative approach with an explanatory research design. The study population included all ASN protocol employees, with a sample of 66 respondents. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis used Partial Least Squares-Structural Equation Modelling (PLS-SEM) to examine direct and indirect relationships between variables. The research results show that the work environment has a significant positive effect on employee job satisfaction and performance. Job placement according to competencies also has a significant positive effect on both. Job satisfaction has been shown to partially mediate the relationship between the work environment and job placement on performance. In conclusion, performance improvements can be achieved through improved facilities, supportive environmental arrangements, and competency-based placement. The practical implication is strengthening human resource management policies that emphasize training, appropriate placement systems, and improving the quality of the work environment to boost performance and the quality of public services.